TRANSLATION SHIFTS OCCURRENCE IN THE MANDARIN-ENGLISH AND ENGLISH-INDONESIAN TRANSLATION OF “FAIRY TALE” SONG (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
The translation is not only limited to the activity of conveying the meaning from one language to the other language. When a text is translated, the form and language system may also be shifted because every language has its unique characteristics. This shift may confuse new language learners who usually translate a text in a literal way. Analyzing the shifts that occurred in different language pairs could show the process of how the form was shifted between these languages. This research analyzes the comparison of translation shifts found in Mandarin-English translation and English-Indonesian translation of the song “Fairy Tale” by Michael Wong. A song is chosen to be analyzed because the method of learning a new language from popular songs is often recommended, and Michael Wong’s “Fairy Tale” fits the criteria. This paper applied a qualitative research method in analyzing the data. The data of Mandarin-English lyric translation was obtained from the subtitle or the transcription in the official music video of Michael Wong’s “Fairy Tale” on YouTube. The data of the English-Indonesian lyric translation was obtained from the same official music video by using the auto-translate feature provided on YouTube. Catford’s theory regarding translation shift was used to analyze the obtained data. Based on the analyzed data, the intra-system shift is expected to occur the most in both of the different language pairs as a result of the different language systems possessed by each of the languages.